The 12 September 2016 ML5.8 midcrustal earthquake in the Korean Peninsula and its seismic implications - Tae‐Kyung Hong; Junhyung Lee; Woohan Kim; In‐Kyeong Hahm; Nam Chil Woo; Seongjun Park (Geophysical Research Letters)
Abstract The seismicity in the Korean Peninsula has increased since the 2011 Mw9.0 Tohoku‐Oki megathrust earthquake. Two strike‐slip earthquakes with magnitudes of ML5.1 and 5.8 occurred in the southeastern Korean Peninsula on 12 September 2016. The two events occurred within 48 min. The ML5.8 earthquake was the largest event in the Korean Peninsula since 1978 when national seismic monitoring began. Both events produced strong high‐frequency ground motions. More than 500 aftershocks with local magnitudes greater than or equal to 1.5 followed the events for 2 months. An unreported subsurface strike‐slip fault with a dip of 65° to the east and a strike of N27°E was responsible for the earthquakes. The fault ruptured at depths of 11–16 km, resulting in a rupture plane of ∼26 km2. The aftershock distribution displayed horizontal streaks at a depth of ∼14 km, which was consistent with the focal mechanism solutions from long‐period waveform inversion. The number of aftershocks decreased exponentially with time. The two ML5.1 and 5.8 earthquakes produced regional Coulomb stress changes of −4.9 to 2.5 bar. The spatial distribution of the aftershocks correlated with the Coulomb stress changes. The peak dynamic stress induced by strong ground motions reached 14.2 bar. The groundwater levels changed coseismically in some regions of decreased static stresses. The earthquakes on previously unidentified faults raised attention for the potential seismic hazards by earthquakes with long recurrence intervals.